Peningkatan Literasi Sains Peserta Didik Melalui Model Pembelajaran Problem Based Learning (PBL) pada Pembelajaran Biologi Konsep Sistem Imun di Kelas Xi Sma Negeri 5 Kota Serang - Khasanah, Uswatun (Fakultas Tarbiyah IAI Nasional Laa Roiba, 2024)
This research aims to determine how the application of problem-based learning (PBL) model in learning Biology on the concept of immune system to improve science literacy. This research is a class action research conducted in 2 cycles in class XI SMA Negeri 5 Kota Serang. This research consists of planning, action, observation and reflection stages in each cycle. The research subjects were students of class XI MIPA 6 SMA Negeri 5 Kota Serang. Data and data sources used were obtained from teachers, students and documentation. Data collection techniques include tests, observation. The results obtained in the implementation of class action research show that the problem-based learning model is a model that can be implemented in Biology learning to improve students' science literacy. In cycle I, the average score of science literacy skills was 70.75. The average value of students' science literacy skills in cycle II was 80.51. Thus, it can be concluded that the problem-based learning model can be used as one of the learning designs to improve students' science literacy skills. Keyword: Scientific literacy, Problem Based Learning, Immune System